Adoption : parents' perceptions of facilitating factors and challenges in the development of the relationship with their baby - Henwood, Penelope (Department of Social Development, 2016)
The study explored the experiences of parents around their adoption process and relationship-building with their babies. It considered their motivation to adopt and their expectations of what that would entail. Challenges and facilitating factors were examined with regards to how their relationship with their child, rarely new born when placed, grew and developed. The study used Ecological and Attachment theories as theoretical frameworks. This research was conducted using a qualitative research design. Twenty participants (ten adoptive couples) were selected using purposive sampling by an adoption agency and interviewed from a semi-structured interview schedule. Each interview was recorded using a Dictaphone and transcribed by the researcher. Data was thereafter analysed using qualitative methods, specifically analytic induction and open coding. The findings of this study highlighted the complexities of the non-normative transition to adoptive parenthood necessary for many who expected to become parents naturally. The stressors involved include micro and macro preferences for biological kin, fears of not being able to love a child not born to oneself and insecurity around the child returning to their biological parents. It was found that the screening process played a valuable role in lessening these fears, creating support structures and working through loss related to infertility.